Environmental Valuation of Investment Projects With Point of Production Approach:KorudanlÄk Gold-Silver Mine Project in Turkey. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Monetary valuation of changes in environmental quality has a great importance in evaluation of investment projects.The benefit or avoided damage cost from a project to change environmental quality is captured by individuals' wilingness to pay(WTP). Valuation methods based on WTP can mainly be categoriesed in two groups as 'production approach' and 'utility approach'. In this study, concept of wilingness to pay and valuation methods based on 'production approach' are investigated with an application to a mine project in Turkey.